فن تشويه المنظور وجمالياته التحريفية وأثره على البعد الإدراكي للعمل في فن التصوير - الطبال، صفا محمد عبده (جمعية إمسيا التربية عن طريق الفن, 2019)
ظهر "مصطلح الخيال المشوه Ana – morphosis في القرن السابع عشر، ويعرض الخيال المشوه على أنه خداع بصري أو خدعة جديدة في الفن، بدأت في عصر النهضة مع إعادة اكتشاف المنظور، وذلك عن طريق تحريف (تشويه) المنظور بحيث يمكن إعداد لوحة قد تظهر بلا معنى حتى ينظر إليها من زاوية معينة فيظهر الشكل طبيعياً. وفي القرن السابع عشر والثامن عشر تطور فن التشويه Ana morphosis نظرياً وعملياً، فقد أصبحت فأصحبت القواعد الهندسية للتشويه مفهومة بشكل أفضل مما جعل التقنيات أكثر دقة وكفاءة وأسهل في بناء تصميمات بصرية كبيرة ومشوهة لجدران وسقوف المباني، فقد استخدمت مدرسة التشويش الانعكاس من المرايا المنحنية على شكل أسطوانات – مخروط – أهرامات من خلال عمل تحول مشوه لشبكة مربعات باستخدام علاقات رياضية تخضع له كافة عناصر العمل الفني حتى يحث ما يسمى بالتشويه، لقد استفاد البحث من القواعد الهندسية لفن التشويه جنباً إلى جنب مع ناتج الشكل على السطح العاكس لأحداث تحريفات وتشويهات جمالية بالأشكال، ومن هنا تتحدد مشكلة البحث في التساؤل الآتي: مشكلة البحث: ما أثر الجماليات التحريفية لفن التشويه على البعد الإدراكي للعمل في فن التصوير؟ أهداف البحث: 1. الاستفادة من ناتج انعكاس الشكل على السطح العاكس للأسطوانة وما ينتج عنه من تحريفات. 2. دراسة نظرية تحريف المنظور لدى جماعة الخيال المشوه والخروج منها بأعمال لها نفس الطابع. نتائج البحث: • نتائج التجربة الأولى: جاءت الخطوط المائلة المنحنية في أسفل العمل كخطوط مرشدة إلى مركز السيادة، ظهرت الأشكال وكأنها تبدو في حالة ضعف وانحلال واسترخاء بحيث تبدو وكأنها قد بدأت بالذوبان، أثارت الانحناءات المتكررة في العمل إحساساً بالحركة، حتى جاء التكوين المنحنى يرمز إلى الهدوء وإيقاع وما لانهاية. • جاءت نتائج التجربة الثانية: تظهر أن اندماج الألوان وتداخلها بصورة عبر عن حركة متطورة بانتظام، من شأنه يبعث إحساس بالراحة والهدوء، كما أحدث تأثيراً قوياً في إظهار استدارة الأجسام الكروية، أثار التكوين الدائري إحساس بالأبدية واللانهائية.
The term "Ana-morphosis" has emerged in the seventeenth century where the Anamorphosis is displayed as it is optical illusion or new trick in the art that started in the renaissance period with the rediscovery of prospective through disport (deform) the prospective in order to prepare a tableau manifested without meaning to be seen from certain angel so the shape appears normal. This kind of Anamorphic art was crystallized in the sixteenth century by a group of members of Mannerism where using the revisionist potentials of mirrors in producing anamorphic images reflect different denotations and provide very strange and amazing plastic solutions, as many artists throughout the age several artistic works that show what the reflective surfaces causing of distortion and perversion in the shape. In the seventeenth and eighteenth century, the Ana-morphosis has theoretically and practically evolved, as the geometrical rules of ana-morphosis art became better understood, the matter which made, the techniques more accurate and efficient and easier to build large visual designs and disported for the walls and ceilings of the buildings. The school of confusion used the reflection through the curved mirrors on shape of cylinders – cone – pyramids via making anamorphic transformation of square lattice using mathematical correlations for which all the elements of artistic work are subjected until occurrence of what is called “ana-morphosis". The research utilized of the geometrical rules of anamorphic art coupled with the shape output on the reflective surface to bring about aesthetic distortions and perversions in the shapes, hence the research problem is determined in the following question: Research Problem: What is the impact of the revisionist aesthetics of anamorphosis on the cognitive dimension for working in the art of portrayal? Research findings: • The results of first trial: the crooked curved lines were displayed in the bottom of the artistic work as guiding lines to the hegemony center while the curvature of lines, plenty rotation of blocks and areas, the disappearance of shapes’ marginality helped to manifest the shapes as they seem in a state of weakness, decay and relaxation to look as they start to soluble, but the frequent curves in the artistic work provoked a feeling of motion till the curved formation came to symbolize the calm, rhythm and infinity. • The results of second trial: they came to manifest the fusion and overlapping of colors through an image expressing regularly developed movement that gives a sense of comfort and calm and it also caused a strong influence in manifesting the rotation of spherical objects and impacts of circular formation that gives a sense of eternality and infinity.
Keywords: الخداع البصري -- فن التصوير -- الفنون التشكيلية